What are the information needs of people with dementia and their family caregivers when they are admitted to a mental health ward and do current ward patient information leaflets meet their needs? - Emma Wolverson; Karen Harrison Dening; Zoe Gower; Pat Brown; Julie Cox; Victoria McGrath; Amy Pepper; Jane Prichard (Wiley, 2023)
Abstract Introduction An admission to a mental health ward is an uncertain and unexpected part of a person's journey with dementia and consequently, families require information about what to expect and how to prepare. This study aimed to establish the information needs of people with dementia and their families at the point of admission to a mental health ward and to collate existing ward information leaflets to explore if they meet these information needs. Methods This research was conducted in two parts: (1) a qualitative study using focus groups, one with people with dementia and family carers with lived experience of such an admission (n = 6), and another with Admiral Nurses (n = 6) to explore information needs at the point of admission. (2) Each National Health Service (NHS) mental health trust (n = 67) was asked to provide a copy of their ward information shared at admission. A total of 30 leaflets were received from 15 NHS trusts; after removing duplicates, 22 were included. A content analysis was conducted to evaluate to what extent leaflets met the information needs identified by focus groups. Results Two main categories 'honest, accurate and up‐to‐date information' and 'who is the information for' and four subcategories were derived from focus group data. Participants felt that people with dementia and their families were likely to have different information needs. Material for people with dementia needed to be in an accessible format. Information should cover the aim of the admission, a timeline of what to expect and details about how families will be involved in care. Practical information about what to pack and ward facilities was valued. Participants spoke about the need to consider the tone of the information, given that people are likely to be distressed. The information leaflets reviewed did not meet the information needs identified by focus group participants. Conclusions People with dementia and family carers have different information needs at the point of admission to a mental health ward. Information provided to people with dementia needs to be in an accessible format with content relevant to these needs. Wards should aim to co‐create information to ensure that they meet people's information needs. Patient or Public Contribution This research was supported by a patient and public involvement (PPI) group of people with dementia and carers who have experience in mental health wards. The idea for the study came from the group and was motivated by their experiences. The PPI group helped with the design of the study and took part in the focus groups. The information generated has been written up in this paper, and the knowledge generated has also been used to co‐create a guide for wards on writing their information leaflets and to support the co‐creation of a public information leaflet by Dementia UK about mental health admissions for people with dementia.